2012
DOI: 10.32607/20758251-2012-4-4-58-64
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Fusion Tags for Effective Production of G-Protein-Coupled Receptors in Bacterial Cell-Free Systems

Abstract: G-protein-coupled receptors (GPCR) constitute one of the biggest families of membrane proteins. In spite of the fact that they are highly relevant to pharmacy, they have remained poorly explored. One of the main bottlenecks encountered in structural-functional studies of GPCRs is the difficulty to produce sufficient amounts of the proteins. Cell-free systems based on bacterial extracts fromE. colicells attract much attention as an effective tool for recombinant production of membrane proteins. GPCR production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In 11 reports, 13,15,[17][18][19][20][21]23,25,27,28 a total of 23 detergents were screened for their solubilization efficiencies (Supporting Information Table S4). Systematic solubilization trials 25 using a homologous series of phosphocholine detergents showed that protein yield increases with chain length, mirroring the dependence of conformational stability on micelle thickness (Figure 4a).…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 11 reports, 13,15,[17][18][19][20][21]23,25,27,28 a total of 23 detergents were screened for their solubilization efficiencies (Supporting Information Table S4). Systematic solubilization trials 25 using a homologous series of phosphocholine detergents showed that protein yield increases with chain length, mirroring the dependence of conformational stability on micelle thickness (Figure 4a).…”
Section: ■ Discussionmentioning
confidence: 99%
“…For instance, the membrane pore of staphylococcal α-hemolysin remains functional after truncation of large parts of its transmembrane domain, and amphipathic peptides rich in cationic and anionic residues may form membrane-spanning charge zippers . An even more drastic example is Mistic, an unusual Bacillus subtilis protein that is essential for biofilm formation and is biotechnologically exploited as a fusion tag to support the membrane targeting, insertion, and detergent-mediated solubilization of other membrane proteins. , Mistic comprises 110 residues that are arranged into a four-helix bundle exposing numerous polar and charged residues (Supporting Information Figure S1), which is incompatible with a transmembrane topology. Having a predicted pI of 4.5, a net charge at pH 7.0 of −12, and a mean hydrophobicity on the normalized Kyte/Doolittle scale of 0.43, Mistic should be more hydrophilic than typical soluble globular proteins and might even be expected to be an intrinsically disordered protein .…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, fusion tags can have different functions including enhancing heterologous protein expression when placed at the N-terminus ( Haberstock et al, 2012 ; Ki and Pack, 2020 ). This allowed, for instance, to increase yields of a GPCR 5–38 times, resulting in sufficient protein amounts for structural-functional studies ( Lyukmanova et al, 2012b ). Most fusion proteins have added sequences encoding an affinity tag that can be added at either end of the cDNA; small tags may also be added by primer extension PCR.…”
Section: Use Of Affinity Tagsmentioning
confidence: 99%
“…Expression efficiency in a cell-free system sometimes depends on an N-terminal tag used, with TrxA and some smaller tags, like T7-tag, being most successful ( Ishihara et al, 2005 ; Haberstock et al, 2012 ; Lyukmanova et al, 2012 ). This is explained by different secondary structure of the corresponding mRNA affecting the translation efficiency.…”
Section: Expressionmentioning
confidence: 99%